Financial Fragmentation and Economic Growth in Europe - Isabel Schnabel; Christian Seckinger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Using industry data from Eurostat and applying the Rajan-Zingales methodology, we investigate the real growth effects of banking sector integration in the European Union. Our sample stretches from 2000 until 2012 and includes the phase of rapid financial integration before the crisis as well as the following phase of financial fragmentation and bank deleveraging. We find evidence that banking sector integration had a more than four times stronger growth effect during the crisis than in normal times. Growth effects are also stronger in times of domestic bank deleveraging. We conclude that concerns of European policy makers about fragmentation in the European banking sector are justified and that future reintegration is an important building block of future growth perspectives in the European Union.
Keywords: F36; G01; G15; 330